Examining the Relationship between Psychosocial Work Factors and Musculoskeletal Discomfort among Computer Users in Malaysia. - Zakerian, S. A.; Subramaniam, I. D. (Iranian Journal of Public Health, 2011)
Background: With computers rapidly carving a niche in virtually every nook and crevice of today's fast-paced society, musculoskeletal disorders are becoming more prevalent among computer users, which comprise a wide spectrum of the Malaysian population, including office workers. While extant literature depicts extensive research on musculoskeletal disorders in general, the five dimensions of psychosocial work factors (job demands, job contentment, job control, computer- related problems and social interaction) attributed to work-related musculoskeletal disorders have been neglected. This study examines the aforementioned elements in detail, pertaining to their relationship with musculoskeletal disorders, focusing in particular, on 120 office workers at Malaysian public sector organizations, whose jobs require intensive computer usage. Methods: Research was conducted between March and July 2009 in public service organizations in Malaysia .This study was conducted via a survey utilizing self-complete questionnaires and diary. The relationship between psychosocial work factors and musculoskeletal discomfort was ascertained through regression analyses, which revealed that some factors were more important than others were. Results: The results indicate a significant relationship among psychosocial work factors and musculoskeletal discomfort among computer users. Several of these factors such as job control, computer-related problem and social interaction of psychosocial work factors are found to be more important than others in musculoskeletal discomfort. Conclusion: With computer usage on the rise among users, the prevalence of musculoskeletal discomfort could lead to unnecessary disabilities, hence, the vital need for greater attention to be given on this aspect in the work place, to alleviate to some extent, potential problems in future.